Kashaura karimba” innovation and hybridization of mbira Instrumentin Zimbabwe: the birth of Karimbashauro - Matiure, Perminus (Midlands State University, 2015)
Technological development in the construction of musical instruments has enabled mbira makers to produce various hybrids of mbira by adding keys to indigenous mbiras. The aim was to enrich the sonic efficacy of the instruments. Consequently this led to the birth of several types of mbiras like hera, munyonga, mbira dzavadzimu, njari, karimba, ndimba, dzvandau, matepe common in Zimbabwe today. Although these mbiras differ in a number of ways, they all retain the core keys of karimba. As a mbira player by inheritance, the writer posits that any additional key/s to a mbira can make the instrument produce new sonority different from the former and this gives birth to a new hybrid. Several mbira researchers like Andrew Tracey concur that the need for the mbira player to improve the resultant sound of his/ her mbira together with technological advancement are the driving forces behind innovation of mbira hybrids. The writer has been playing and teaching kwanongoma karimba commonly known as nyunganyunga since 2005 and discovered that the instrument could not produce lead line, kushaura which is a common feature in the Shona mbira music. For instance when playing pieces like nhemamusasa and taireva on Kwanongoma karimba one would notice that the top register is limited such that it is impossible to play the traditional descending lead melody. It is against this background that the writer prompted to improve on the existing karimba to enable the instrument to play the lead in a more surrogative manner hence the innovation of karimbashauro. This paper will trace the evolution of karimbashauro from kwanongoma karimba and unpack the temperament of the new innovation by employing a comparative analysis approach. The bulk of the data informing this paper is drawn from a field study carried in Hwedza District, Kwanongoma in Bulawayo and Mbira Centre in Harare. An ethnographic paradigm was adopted in which participant observation and face-to-face interviews were used to solicit data about mbira in general and kwanongoma karimba in particular.